Organic Pollutants in the Geosphere - Schwarzbauer, Jan (Fundamentals in Organic Geochemistry,, 2018)
This third volume focusses on anthropogenic organic pollutants harming the environment. Their structural diversity and fate in the environment, their effects and relevance are presented. For such a flexible usage this textbook series 'Fundamentals in Organic Geochemistry' consists of different volumes with clear defined aspects and with manageable length. Organic Geochemistry is a modern scientific subject characterized by a high transdisciplinarity and located at the edge of chemistry, environmental sciences, geology and biology. Therefore, there is a need for a flexible offer of appropriate academic teaching material on an undergraduate level addressed to the variety of students coming originally from different study disciplines.